2019
DOI: 10.1186/s12944-019-1046-z
|View full text |Cite
|
Sign up to set email alerts
|

Several circulating miRNAs related to hyperlipidemia and atherosclerotic cardiovascular diseases

Abstract: Background In recent years, an increasing number of studies have proved that circulating miRNAs could be used for the early diagnosis of cardiovascular diseases and even play vital roles in the evaluation of therapeutic effects or prognosis. This study was conducted to examine the correlation between serum microRNAs and hyperlipidemia to provide a theoretical basis for the early screening and intervention of atherosclerotic cardiovascular diseases (ASCVD). Methods The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
(29 reference statements)
1
16
1
1
Order By: Relevance
“…Initial miRNA-associated studies were mainly focused on cancer development, cardiovascular diseases, and metabolic diseases. It was found that the expression profile of miRNAs was changed in plasma and tissue samples under disease conditions such as cancer [11], hyperlipidemia [12], hyperglycemia [13], endothelial cell dysfunction [14] and diabetes [15]. We also identified the altered expression of circulating miRNAs in patients with coronary heart disease (CHD), compared with healthy…”
Section: Introductionmentioning
confidence: 99%
“…Initial miRNA-associated studies were mainly focused on cancer development, cardiovascular diseases, and metabolic diseases. It was found that the expression profile of miRNAs was changed in plasma and tissue samples under disease conditions such as cancer [11], hyperlipidemia [12], hyperglycemia [13], endothelial cell dysfunction [14] and diabetes [15]. We also identified the altered expression of circulating miRNAs in patients with coronary heart disease (CHD), compared with healthy…”
Section: Introductionmentioning
confidence: 99%
“…NIHSS score was higher in IS patients with the A/A genotype of rs79402775 than with the G/G or G/A genotypes. A recent study showed that miRNA-933 was significantly decreased in the peripheral circulation of patients with hyperlipidemia and with atherosclerotic cardiovascular diseases (ASCVD) [31]. Thus, authors suggested circulating miRNA-933 as a feasible predictor for ASCVD at the early stage [31].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that miRNA-933 was significantly decreased in the peripheral circulation of patients with hyperlipidemia and with atherosclerotic cardiovascular diseases (ASCVD) [31]. Thus, authors suggested circulating miRNA-933 as a feasible predictor for ASCVD at the early stage [31]. On the contrary, other study reported that 27-hydroxycholesterol, a cholesterol metabolite, increased the level of miRNA-933 in microvascular endothelial cells along with the elevation of TNF- α and IL-6 [32].…”
Section: Discussionmentioning
confidence: 99%
“…表达升高, 并与血浆TC水平呈正相关; miR-122及miR-34a表达升高, 并与血TG及VLDL-C水平正相关. Xu等 人 [16] 分析了高脂血症患者和健康受试者循环miRNA 的表达, 发现miR-933可能与高LDL-C有关. Guo等 人 [38] 发现, 高脂血症患者血清中miR-587的表达较健 康对照中的降低, 并与血TC负相关.…”
Section: 循环Mirna及其来源、分类unclassified